The Matthew effect in running: an analysis of elite endurance athletes over 23 years - Thuany, M.; Knechtle, B.; Kipchumba, K.; Hill, L.; Gomes, T. N. (Journal of Science in Sport and Exercise, 2023)
Purpose The purpose of this study was to investigate the frequency of countries represented in the TOP20 long-distance elite runners ranking during 1997-2020, taking into account the countries` Human Development Index (HDI), and to verify if the Matthew effect can be observed regarding countries` representativeness in the raking alongside the years.